Cooperative Co‐evolutionary Artificial Bee Colony Algorithm Based on Hierarchical Communication Model. Issue 3 (1st May 2016) - Hu, Chunyu; Liu, Hong; Zhang, Peng
Abstract : Canonical Artificial bee colony (ABC) algorithm with a single species is insufficient to extend the diversity of solutions and may be trapped into the local optimal solution. This paper proposes a new co‐evolutionary ABC algorithm (HABC) based on Hierarchical communication model (HCM). HCM combines advantages of global and local communication pattern. With adjustment strategies on species and groups, HCM can reduce the computational complexity dynamically. Performance tests show that the HABC algorithm exhibit good performance on accuracy, robustness and convergence speed. Compared with ABC and Integrated co‐evolution algorithm (IABC), HABC performs better in solving complex multimodal functions.